PELATIHAN PEMBUATAN KONTEN BUDAYA UNTUK INTERNASIONALISASI KEBUDAYAAN MENTAWAI DI SANGGAR PASIGEUGEU PURO 2 - Sari Fitria; Ainul Addinna; Muhammad Ismail (PUAN INDONESIA, 2026)
Mentawai is an island in West Sumatera inhabited by indigenous community that still maintain their culture. However, this origin culture still cannot strongly attract international tourists. Most of these tourists come to Mentawai for surfing. In fact, Mentawai can potentially become a tourism destination that offers authentic culture, primarily through the existence of cultural center created by local people. One of the cultural centers is Sanggar Pasigeugeu Puro 2. This cultural community has made some efforts to promote Mentawai culture through social media. They have uploaded various content about Mentawai culture in Instagram. However, they have lack of skills in to create cultural content that have a good engagement for Instagram users. They also face obstacles in English skills so that they are not able to create English caption for their cultural content. This fact shows that the partner faces problems in creating and producing English-based cultural content for social media to reach international Instagram users. Therefore, this community program is purposed to provide trainings on producing cultural contents and to improve English skills for members of Sanggar Pasigeugeu Puro 2. In this community service, they can enrich their skills in various fields. As a result, they have chances not only to promote Mentawai cultures but also to document them in the forms of photos and videos. The result of this community service shows that the members’ skills in English, photography, and videography has improved that they can produce a more qualified cultural content.